209k views
5 votes
Please help in this question with explanation. pls​

Please help in this question with explanation. pls​-example-1

1 Answer

2 votes

Answer:

V = x³ - 3x² + 3x - 1

Explanation:

The volume (V) of a cube is calculated as

V = s³ ( s is the measure of the side )

Here s = x - 1 , thus

V = (x - 1)³

= (x - 1)(x - 1)(x - 1) ← expand the second pair using FOIL

= (x - 1)(x² - 2x + 1) ← distribute

= x³ - 2x² + x - x² + 2x - 1 ← collect like terms

= x³ - 3x² + 3x - 1

User Tamas Szoke
by
6.0k points